Teknologi Pendidikan dalam Meningkatkan Kualitas Hidup dan Kepatuhan pada Penderita Hipertensi - Firmansyah Firmansyah; Diana Irawati; Melati Fajarini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of educational technology in improving the quality of life and compliance in hypertensive patients. The research method is quasi-experimental, with a research design before and after educational interventions. The results showed that the majority of respondents aged >50 years were ten people (83.3%), female sex was eight people (66.7%), with high school education status were six people (50%), respondents had a history of hypertension numbering ten people (83.3 %), and the maximum BMI value is 25.1-27 of 7 people (58.3%). In conclusion, educational interventions with flipcharts can improve quality of life scores and enhance adherence to hypertension treatment, with attentive listening and dialogue built within health facilities and in community spaces that can facilitate decision-making about strategies to promote life improvements. Keywords: Hypertension, Quality of Life, Educational Technology